2022
DOI: 10.1155/2022/6998276
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Boer × Central Highland Crossbred Bucks and Farmers’ Perceptions on Crossbred Goats in Northeastern Ethiopia

Abstract: The study aimed to characterize the production system, to evaluate the genetic merit of Boer × Central Highland crossbred bucks, and to solicit the perception of farmers about crossbred goats and crossbreeding program. Data were collected through a personal interview, focus group discussion, field observation, and measurement of the live animal. Besides, data on growth performance were extracted from available performance records at Sirinka sheep and goats breeding station. Data were analyzed using SAS, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 14 publications
4
12
1
Order By: Relevance
“…The surveyed participants' perceptions are in line with the observations by Demerew & Aschenaki (2023) that about 73.4% of agro-pastoralists in Bena-Tsemay district greatly give high value for Boer crossbreeds for their sound production performance and better environmental adaptation as their local breeds. Other similar results were also reported by many authors, about 80% of farmers in the Raya Kobo district and about 57.1% of the respondents in the Amhara Sayint district revealed strong attention for crossbreeding reported by Zeleke et al (2022). Although the pastoral and agro-pastoral was preferred to Boer crossbreed breeds they confirmed that the crossbreeds had poor tolerance to feed shortages and endemic diseases.…”
Section: Preference For Crossbreed Goatssupporting
confidence: 83%
See 1 more Smart Citation
“…The surveyed participants' perceptions are in line with the observations by Demerew & Aschenaki (2023) that about 73.4% of agro-pastoralists in Bena-Tsemay district greatly give high value for Boer crossbreeds for their sound production performance and better environmental adaptation as their local breeds. Other similar results were also reported by many authors, about 80% of farmers in the Raya Kobo district and about 57.1% of the respondents in the Amhara Sayint district revealed strong attention for crossbreeding reported by Zeleke et al (2022). Although the pastoral and agro-pastoral was preferred to Boer crossbreed breeds they confirmed that the crossbreeds had poor tolerance to feed shortages and endemic diseases.…”
Section: Preference For Crossbreed Goatssupporting
confidence: 83%
“…In the country, Boer goats are imported from South Africa with the aim of improving the indigenous goat's market weight. This meat goat breed is serving as a sire line for up-grading of indigenous meat goat breeds (Demerew & Aschenaki, 2023;Zeleke et al, 2022). Crossing of local goats with Boer buck and distribution of crossbreeds (50% to 75%) genotypes has been in progress with the initiative of the Ethiopian Sheep and Goat Productivity Improvement Project (ESGPP) and currently Jinka Agricultural Research Center (JARC) has disseminating crossbreed bucks to pastorals and agro-pastoralists to improve the weight gain performance of indigenous breeds.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the reasons of Boer crossbred preferences by respondents were due to its adaptive behavior confirmed by their capability to tolerate shortage of feeds, poor quality forages, drought and diseases. The current study also revealed that the pastorals and agro-pastorals who preferred to keep Boer crossbreds believed that the Boer crossbred grows faster, has a big mature body size, has an attractive phenotype and sold at an exorbitant price in the market compared to the indigenous breed and a similar finding was observed in the study of Zeleke et al (2022) for Boer × Central Highland crossbred goats. The study conducted by Farm-Africa (2022) confirmed that, Boer crossbred kids' fast grower, better efficient in feed conversion and better milk and meat producers compared to indigenous goats, being easier to rise than purebred Boer goats.…”
Section: Perception and Preference Of Pastoral Agro-pastoral On Cross...supporting
confidence: 81%
“…In the current study, some few (21.7%) respondents claimed that the Boer crossbreds unable to survive better in their environment due to need of special management such as indoor feeding and watering, frequent health follow-up and treatment and adequate housing; this makes to be labour intensive and extensive for goat keeper. In contradiction to this Zeleke et al (2022) reported that 77.8% of the respondents do not prefer crossbreeding because of poor adaptability of the crossbred kids in the Habru Woreda. On the other hand, the reasons of Boer crossbred preferences by respondents were due to its adaptive behavior confirmed by their capability to tolerate shortage of feeds, poor quality forages, drought and diseases.…”
Section: Perception and Preference Of Pastoral Agro-pastoral On Cross...mentioning
confidence: 70%
See 1 more Smart Citation